Aniołowie w poezji Adama Mickiewicza - Kulesza-Gierat, Monika (Tow. Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2007)
Zsfassung in engl. Sprache u.d.T.: Angels in Adam Mickiewicz's poetry : an outline of a monograph
Zsfassung in engl. Spr. u.d.T.: Angels in Adam Mickiewicz's poetry
Keywords: Mickiewicz; Adam; Angels in literature